Advancing sustainable livestock practices through ecosystem services valuation - Burkart, Stefan; Florez Herrera, Jesus Fernando (2025)
As the world faces increasing environmental challenges, the need for sustainable livestock practices has never been more urgent. In response to this, a multi-disciplinary team of international researchers from the Alliance of Bioversity International and CIAT, the International Livestock Research Institute (ILRI), and the International Center for Agricultural Research in the Dry Areas (ICARDA) have developed an integral framework for evaluating ecosystem services in livestock farming, aiming to promote practices that balance environmental, economic, and social objectives.